Using information technology to help business students learn about contract law - John S. Edwards; Robert I. Akroyd (Association for Learning Technology, 1995)
Almost all business students study law. However, business students have a different perspective on law from that of law students. A common problem, therefore, in legal courses for business students is how to provide a sufficiently wide-ranging, practically relevant programme without the sacrifice of intellectual depth. At Aston Business School, one approach adopted has been to supplement lectures with role-play exercises, rather than conventional tutorials.